2020
DOI: 10.1002/nano.202000172
|View full text |Cite
|
Sign up to set email alerts
|

ASnX3—Better than Pb‐based Perovskite

Abstract: Organic‐inorganic halide perovskite solar cells (PSCs) have drawn tremendous attention as their power conversion efficiency (PCE) has soared to 25.2%. Yet the most efficient halide perovskite materials all contain the toxic element lead (Pb). The search for an alternative element is a crucial research direction. Among all candidates, tin (Sn) appears to be the most promising one for its nontoxicity and physical similarity to lead (Pb). Herein, we review and summarize recent advancements in this emerging resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 167 publications
0
7
0
Order By: Relevance
“…For instance, as Figure 11 a shows, in the examined case of Br rich CsSnI 3‐ x Br x samples, [ 253 ] I‐rich perovskites demonstrate an orthorhombic phase, while Br‐rich perovskites share a cubic one. [ 203,254 ] In general, replacing I with Br leads to a blueshift of the absorption and IPCE onset, as well as, higher V OC , as Figure 11b demonstrates. The latter happens due to the decrease in Sn vacancies that are inherent with the presence of I.…”
Section: Critical Parameters Under Low Light Environmentmentioning
confidence: 74%
“…For instance, as Figure 11 a shows, in the examined case of Br rich CsSnI 3‐ x Br x samples, [ 253 ] I‐rich perovskites demonstrate an orthorhombic phase, while Br‐rich perovskites share a cubic one. [ 203,254 ] In general, replacing I with Br leads to a blueshift of the absorption and IPCE onset, as well as, higher V OC , as Figure 11b demonstrates. The latter happens due to the decrease in Sn vacancies that are inherent with the presence of I.…”
Section: Critical Parameters Under Low Light Environmentmentioning
confidence: 74%
“…As a result of the crystallization reaction at 80°C, we successfully obtained 5mm-size MAPbBr3 single crystal cubes, as shown in Figure 1(a). Each individual MAPbBr3 crystal was found to grow at a rate of approximately 40 mm 3 /h, which is significantly faster than the growth rates reported in previous methods [21]. Notably, we observed that the crystallization process is reversible for both MAPbBr3 single crystals and Zn-PP passivated MAPbBr3 single crystals.…”
Section: Resultsmentioning
confidence: 41%
“…At room temperature, with the Kirkwood correlation factor g ∼ 1, high-frequency dielectric constant ∼16 (100 kHz), and number density 4.18 × 10 27 m −3 , we obtained a dipole moment of 0.6 D, which is comparable to the magnitude of the dipole moment of a FA + cation estimated from ab initio electronic structure calculation. 11,26,28 Nevertheless, this clearly indicates that the dipolar contribution of polarization in this frequency regime is reflective of the polarization of the FA + cation dipole moment. Interestingly, we do not observe any significant variation of the dielectric constant in this regime, indicating that the dipolar disorder prevalent in MA-based perovskite materials is not present in these perovskites (Figure 2a,d).…”
Section: Resultsmentioning
confidence: 94%
“…In general, we observe a higher magnitude of ε r (1 kHz) for CsFASnI 3 (∼50), which decreases to ∼39 for CsFAPbI 3 (Figure b,e). This can possibly be attributed to the difference in the crystal structure between the Pb- and Sn-based perovskites. , Upon a decrease of the temperature to 200 K, the ε r values decrease to 35 for CsFASnI 3 and ∼22 for CsFAPbI 3 (Figure b,e). This trend is attributed to the freezing of ion migration and the associated ionic polarization with decreased temperature.…”
Section: Resultsmentioning
confidence: 99%